1987
DOI: 10.1139/x87-027
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of large woody debris in streams in old-growth Douglas-fir forests

Abstract: Transfer of large woody debris (>10 cm diameter) from old-growth Douglas-fir (Pseudotsugamenziesii (Mirbel) Franco) forests into five first-to fifth-order stream reaches (drainage areas of 0.1 to 60.5 km2) has ranged from 2.0 to 8.8 Mg•ha−1•year−1 in 7- to 9-year study periods. Amounts of large debris in these streams range from 230 to 750 Mg•ha−1 with generally lower values in larger channels. The addition of woody debris is widely scattered in time and space and comes mainly from single trees rooted away … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
259
3
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(280 citation statements)
references
References 12 publications
16
259
3
2
Order By: Relevance
“…Inputs of large wood for instream habitat complexity: Over the last three decades, extensive literature has documented the hydrological, ecological, and geomorphic effects of instream large wood and reported on the role that large wood plays in linking aquatic, riparian, and upland portions of watersheds (Lienkaemper and Swanson 1987;Bilby and Bisson 1998;Gregory and others 2003a). Large wood strongly influences channel form in small streams, creating pools and waterfalls and affecting channel width and depth (Montgomery and others 2003).…”
Section: Valued Functions Of Riparian Plant Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inputs of large wood for instream habitat complexity: Over the last three decades, extensive literature has documented the hydrological, ecological, and geomorphic effects of instream large wood and reported on the role that large wood plays in linking aquatic, riparian, and upland portions of watersheds (Lienkaemper and Swanson 1987;Bilby and Bisson 1998;Gregory and others 2003a). Large wood strongly influences channel form in small streams, creating pools and waterfalls and affecting channel width and depth (Montgomery and others 2003).…”
Section: Valued Functions Of Riparian Plant Communitiesmentioning
confidence: 99%
“…In five Colorado mountain streams, Wohl and Goode (2008) found that reach-scale wood loads and logjam locations remained relatively constant during an 11-year monitoring study. Although results from other regions vary, instream LW has been shown to be mobile and dynamic, and the physical factors influencing in-channel wood distribution and loads are similar (Lienkaemper and Swanson 1987). Most published studies have presented data on chronic inputs; because tracking individual LW pieces is time-consuming and labor-intensive (Wohl and others 2010), few studies have monitored individual reaches beyond 10 years, particularly the fate of LW pieces following fire and other disturbances.…”
Section: Valued Functions Of Riparian Plant Communitiesmentioning
confidence: 99%
“…2 ) L/8, where D 1 and D 2 ¼ diameters (m) at each end and L ¼ length (m) of the large wood (Lienkaemper and Swanson 1987). The influence of large wood on stream morphology was classified by visual assessment into one or more functional categories as follows: (1) pool formation, (2) sediment storage, (3) step-pool formation, (4) flow deflection, (5) organic matter retention, (6) bank armoring, and (7) having no obvious function (Baillie and Davies 2002).…”
Section: Large Wood Characteristics and Functionsmentioning
confidence: 99%
“…In general, we should expect higher annual variation in upstream watersheds due to the fact that they have less area to capture precipitation events and runoff is relatively peaked. In addition, as is the case with smaller streams, their transport capacity is low due to the relative size of the stream and therefore even with relatively large flows, not all logs in the channel and floodplain are transported due to resistance caused by complex topography, constricted valleys, and small channel widths (Lienkaemper and Swanson, 1987).…”
Section: Export Variability In Small To Medium Sized Watershedsmentioning
confidence: 99%
“…One general pattern to emerge from field and flume studies is that large wood movement is affected by the ratio of piece-size to channel-width and is dependent on the specific channel morphology of a river reach (Lienkaemper and Swanson, 1987;Bilby and Ward, 1989;Nakamura and Swanson, 1994;Braudrick and Grant, 2000). These studies found that smaller wood pieces move more frequently through larger streams that have a Fremier, Page 6 of 39 higher capacity to move larger pieces of wood; however, it has been observed that some pieces are too large or anchored by the bank that transport does not occur even at high flows (Piégay et al, 1999).…”
Section: Introductionmentioning
confidence: 99%